Alasan Permohonan Kasasi Penuntut Umum Terhadap Putusan Lepas Dari Segala Tuntutan Dalam Perkara Kejahatan Terhadap Asal-Usul Dan Perkawinan - Anggi Anindya Wardhani (Verstek, 2017)
Case reviewed at Supreme Court’s Verdict Number 937 K/Pid/2013 is a crime against the origins and marriage. The defendant, who is a Public Servant (PNS) in Bangkinang married for the second time, meanwhile the defendant still has legal wife. Before the marriage, The defendant never ask for permission from his legal wife. The purpose of this research is to understand the reasons of the cassation reasons by public prosecutor and the consideration of Supreme Court judges in examining and deciding the case of crimes against the origins and marriage.    The results showed that The public Prosecutor submit the cassation application with reasons that the law was not occurred necessarily and it’s consistent with Article 253 Criminal Procedure Code about the reasons of Cassation application. The defendant was right proven guilty, then article 256 is applied. Consideration of the Supreme Court’s Judge in examines the cassation application for onslag verdict is based on the Article 256 juncto Article 193.      Keywords: crime against the origins and marriage, cassation reasons, public prosecutor, consideration of the judge